The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0034-70942008000600001
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre anestesia peridural torácica e anestesia geral em mastectomia oncológica

Abstract: Rev Bras AnestesiolARTIGO CIENTÍFICO 2008; 58: 6: 561-568 SCIENTIFIC ARTICLE RESUMO Belzarena SD -Estudo Comparativo entre Anestesia Peridural Torácica e Anestesia Geral em Mastectomia Oncológica. JUSTIFICATIVA E OBJETIVOS:A anestesia peridural torácica é utilizada com freqüência para procedimentos estéticos da mama e há poucos relatos de seu emprego para mastectomias com exploração axilar. O presente estudo comparou a técnica com anestesia geral em operações oncológicas da mama. MÉTODO: CONCLUSÕES:A técni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…The combination of regional anesthesia and general anesthesia may result in significant hemodynamic fluctuations [ 34 ], potentially causing serious adverse events such as asystole [ 35 ]. The TPVB can be thought of as a unilateral thoracic epidural block, and there are few if any clinically significant hemodynamic effects in patients following mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of regional anesthesia and general anesthesia may result in significant hemodynamic fluctuations [ 34 ], potentially causing serious adverse events such as asystole [ 35 ]. The TPVB can be thought of as a unilateral thoracic epidural block, and there are few if any clinically significant hemodynamic effects in patients following mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, surgical intervention is more conservative, but in most cases, partial or total mastectomy associated with axillary exploration to remove lymph nodes for staging or immune-chemical testing is still necessary. [1] General anesthesia is currently the standard technique used for surgical treatment of breast cancer. The drawbacks of general anesthesia include, but not limited to, inadequate pain control due to a lack of residual analgesia, high incidence of nausea and vomiting, and increasing the length of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Bhosle et al 5 documented hypotension warranting the use of vasopressors in 23.33% of their patients; no shivering, nausea or vomiting was recorded. In contrast, Balzarena et al 11 reported a high incidence of hypotension (60%) in 20 patients who required TEA for mastectomy; also, pruritus and vomiting were recorded postoperatively. This difference may be due to differences in the epidural drug dosing and blood loss during the procedure.…”
Section: Discussionmentioning
confidence: 90%
“…This high success rate is comparable to previous studies, which reported 100% success in their series. 5,11 In this study, TEA was applied to a variety of surgical procedures with specific anaesthetic considerations including laparotomy for intestinal obstruction and nephrectomy, thus demonstrating the versatility of epidural anaesthesia. Similarly, Bhosle et al 5 in a previous retrospective study demonstrated the feasibility and safety of TEA in a variety of upper and lower abdominal surgeries including emergency procedures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation